PENGARUH MODERNISASI SPLINTER TERHADAP ISLAM DI KELURAHAN IV DESA MEDAN TIMUR, KECAMATAN MEDAN DENAI - amanda putri, Astri; Harahap, Indra (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This study examines the impact of modernization on the flow of splinters in Islam, especially in Menteng Village, Medan Denai District. The modernization process resulted in major changes in the religious context in Indonesia, which is known for its diversity of religions and beliefs. The school of deviation, which usually emerged in response to traditional understandings, is faced with new challenges and opportunities in this modern age, with modernization affecting the practices and values accepted by its adherents. However, modernization can also create tensions between traditional norms and the ever-changing needs of the times, creating complex dynamics in which fringe currents must adapt to social and cultural progress. This research aims to understand how social, economic, and technological changes affect the religious practices and understanding of splinters, with the hope of harmonizing traditional values and modernity, so that splinters can contribute positively to a more inclusive and adaptive Islamic society.